Changes in Brain Matrix Glycan Sulfation Associate With Reactive Gliosis and Motor Coordination in Mice With Head Trauma - Alonge, Kimberly M.; Herbert, Melanie J.; Yagi, Mayumi; Cook, David G.; Banks, William A.; Logsdon, Aric F. (Frontiers in Behavioral Neuroscience, 2021)
Perineuronal nets (PNNs) are extracellular matrix (ECM) structures that enmesh and regulate neurocircuits involved in motor and sensory function. Maladaptive changes to the composition and/or abundance of PNNs have been implicated in preclinical models of neuroinflammation and neurocircuit destabilization. The central nervous system (CNS) is limited in its capacity to repair and reorganize neural networks following traumatic brain injury (TBI) and little is known about mechanisms of ECM repair in the adult brain after TBI. In this study, adult male C57BL/6 mice were subjected to a TBI via a controlled cortical impact (CCI) to the right motor and somatosensory cortices. At 7 days following CCI, histological analysis revealed a loss of Wisteria floribunda agglutinin (WFA) positive PNN matrices in the ipsilateral cortex. PNNs are comprised of chondroitin sulfate (CS) and dermatan sulfate (DS)-glycosaminoglycans (GAGs), the composition of which are known to influence neuronal integrity and repair. Using an innovative liquid chromatography tandem mass spectrometry (LC-MS/MS) method, we analyzed the relative abundance of six specific CS/DS-GAG isomers (∆4S-, ∆6S-, ∆4S6S-, ∆2S6S-, ∆0S-CS, and ∆2S4S-DS) from fixed-brain sections after CCI injury. We report a significant shift in CS/DS-GAG sulfation patterns within the rostro-caudal extent of the injury site from mice exposed to CCI at 7 days, but not at 1 day, post-CCI. In the ipsilateral thalamus, the appearance of WFA+ puncta occurred in tandem with gliosis at 7 days post-CCI, but weakly colocalized with markers of gliosis. Thalamic WFA+ puncta showed moderate colocalization with neuronal ubiquitin C-terminal hydrolase L1 (UCHL1), a clinical biomarker for TBI injury. A shift in CS/DS-GAG sulfation was also present in the thalamus including an increase of 6S-CS, which is a specific isomer that associates with the presence of glial scaring. Upregulation of the 6S-CS-specific sulfotransferase (CHST3) gene expression was accompanied by reactive gliosis in both the ipsilateral cortex and thalamus. Moreover, changes in 6S-CS extracted from thalamus positively correlated with deficits in motor coordination after CCI. Collectively, these data argue that CCI alters CS/DS-GAG sulfation in association with the spatiotemporal progression of neurorepair. Therapeutic interventions targeting restoration of CS/DS-GAG sulfation patterns may improve outcomes from TBI.